Pilgrimage and Cultural Heritage: Understanding Tourist Motivations at the Tomb and Sunan Drajat Museum at Lamongan East Java-Indonesia - Nuruddin; Putu Eka Wirawan; Putu Herny Susanti; Nashihin; Luh Yusni Wiarti; Dahlan Abdullah (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2026)
Motivation is a key factor in tourists’ decision-making, including visits to historical sites related to the development of religion. This study aims to analyze the motivation of tourists visiting historical sites such as the tombs of saints and museums preserving their legacy. A qualitative method with a thematic and interpretive approach was used. Data were collected through interviews, field observations, and literature review. The findings reveal two main motivational perspectives: religious and cultural. Religious motivation includes the pursuit of blessings, spiritual merit, and inner peace, while cultural motivation involves interest in history, architecture, and cultural heritage. This study offers both theoretical and practical contributions to the development of tourism based on local and spiritual values. Its uniqueness lies in combining religious and cultural motivations in the context of visits to the Tomb and Museum of Sunan Drajat Lamongan—a site that has received little scholarly attention. Unlike previous studies that tend to separate the two aspects, this research integrates spiritual and historical dimensions to better understand tourist behavior.